(untitled) - Rider, Michael J (New York, 2013)
This textbook is intended as a classroom text or a self-paced tutorial for the person who wants to learn Creo Parametric 1.0, formerly known as ProEngineer Wildfire and Mechanica. This textbook discusses design intent while you are learning, and at the same time, it shows how knowledge covered in some basic engineering courses such as: statics, dynamics, strength of materials, and design of mechanical components can be applied to design. You do not need an engineering degree nor be working toward a degree in engineering to use this textbook.
Keywords: Computer aided desing,Three-dimensional imaging,Máy tính hỗ trợ thiết kế,Hình ảnh ba chiều